Evaluation of the state of Project Management in the advertising industry : "The soft stuff is the hard stuff" - Frank Arthur Blöndahl Cassata 1983- (2018)
In this paper the current state of Project Management in the advertising industry in Iceland is evaluated. A qualitative research method was used to gather information by conducting interviews with executives and key employees from a cross-section of the industry. A quantitative method was also employed in an attempt to define the industry's culture based on a chosen culture model. A thematic analysis of the interviews revealed several challenges facing the industry. These challenges can be classified into three categories: organisational culture, communications and teamwork. Improvement opportunities based on these challenges are presented and discussed. Keywords: Organisational Culture, Communications, Teamwork, Team Development, Psychological Safety, Project Management Competences, Leadership.